The mechanism of macroautophagy: The movie - Fulvio Reggiori; Patricia Boya; David da Costa; Zvulun Elazar; Eeva-Liisa Eskelinen; Judith Farrés; Sebastian Guettler; Claudine Kraft; Heinz Jungbluth; Ana Martinez; Etienne Morel; Ole Pless; et al. (Autophagy Reports, 2022)
This animated movie presents the mechanism of macroautophagy, hereafter autophagy, by showing the molecular features of the formation of autophagosomes, the hallmark organelle of this intracellular catabolic pathway. It is based on our current knowledge and it also illustrates how autophagosomes can recognize and eliminate selected cargoes.